(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
The German Studies (GS) programme has been offered since 1981 at the University of Nairobi (UoN), 1986 at Kenyatta University (KU), and 2009 at Moi University. By now, the programme should have come of age and be producing enough language experts and teachers to supply the growing number of schools (currently 82) offering German. Available data show that GS students are so marketable that they are often offered employment before they have completed their university studies. So, the question that arises is why student enrolments for the subject are not rising accordingly, in particular at the University of Nairobi. This paper discusses answers to this question and proposes strategies that should be undertaken to increase student enrolments.